Contribution to the management system of the laboratory of construction materials of the civil construction course of CEFET-RJ - Carvalho, Rebeca Waltenberg de; Tozatto, João Hermem Fagundes (Seven Editora, 2023)
The construction industry accounts for 15 to 50% of the consumption of natural resources extracted on the planet (FINESTRA, 2009). As a result, many of these raw materials are currently in short supply. The production of building materials also contributes significantly to the pollution of the planet, with the release of gases and dust into the atmosphere. In addition, construction is the largest producer of waste in the entire society. In Brazil, most of this waste goes to inadequate deposits (often clandestine), which contributes significantly to the degradation of the ecosystem (PORTAL COMPET, 2006). This project rethought the use of the laboratory of building materials, characterizing the useful space – its functionality, the activities carried out there, limitations – as well as the materials used. From a diagnostic study carried out, criteria were established for a better management of the same and possibilities were studied regarding the reduction of the amount of materials and inputs used in the classes, prioritizing the reuse and/or recycling of all or most of them. In addition, it is expected that this research will stimulate students of technical courses in civil construction (buildings and roads) to understand the role of environmental management – both in the academic environment and on a construction site. Thus, when inserted in the labor market, they become multipliers and promote a gradual change from the current and expensive methods used today. DOI:https://doi.org/10.56238/alookdevelopv1-096